Bangladesh : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bangladesh. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses key issues pertaining to the economy of Bangladesh. Macroeconomic stability has been maintained since the last Article IV Consultation in November 2013. But like other Asian countries, private domestic demand, credit growth, and export growth have been tepid. The economy of Bangladesh has undergone a major transformation in the past two decades. Due to the political stability in this country, public investment is ramped up and constraints on private investment are eased, and growth is projected to accelerate gradually to 7 percent. Policies to safeguard stability, boost private investment, strengthen inclusion, and create fiscal space are emphasized in this paper.